2016
DOI: 10.1159/000452790
|View full text |Cite
|
Sign up to set email alerts
|

Sparing Surgery for the Successful Treatment of Thyroid Papillary Carcinoma Invading the Trachea: A Case Report

Abstract: Published reports on salvage treatment for trachea reconstruction after total thyroidectomy or partial tracheotomy are available, some of them using structures of the trachea itself, auricular cartilage, a musculocutaneous flap, or other methods. In our report, we emphasize the importance of a search for a new material and approach for sparing surgery. The purpose of this article is to describe a case of a successful sparing surgery in a patient with advanced thyroid papillary carcinoma invading the trachea. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
(20 reference statements)
1
9
0
3
Order By: Relevance
“…The positive interaction between the KTNM and surrounding tissues was previously studied in animal models [7,26], and it was also assessed clinically in 120 cancer patients, as reported in Refs. [10,27], where the survivability of KTNM placed in highly virulent media was highlighted. The said studies indicated that the formation of bone tissue occurred through indirect osteogenesis: loose connective tissue followed by the formation of dense semi-formed connective tissue, which was replaced by fibrocartilage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive interaction between the KTNM and surrounding tissues was previously studied in animal models [7,26], and it was also assessed clinically in 120 cancer patients, as reported in Refs. [10,27], where the survivability of KTNM placed in highly virulent media was highlighted. The said studies indicated that the formation of bone tissue occurred through indirect osteogenesis: loose connective tissue followed by the formation of dense semi-formed connective tissue, which was replaced by fibrocartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Based on preoperative planning, the customized endograft is fabricated following the volume of upcoming repair as recommended in References [7,10,27]. Each KTNM is made of the TN-10 alloy superelastic filaments (60 µm in diameter), having a microporous, oxicarbonitride superficial layer [29,30].…”
Section: Methodsmentioning
confidence: 99%
“…Denis Evgen'evich KULBAKIN 1,2,3,4 , Evgeniy Lkhamatsyrenovich CHOYNZONOV 1,2,3,5 , Nadezhda Viktorovna CHERDYNTSEVA 1,4 , Evgeniy Nikolaevich BOLBASOV 5 , Valeriy Anatol'evich SVETLICHNYI 4 , Ivan Nikolaevich LAPIN 4 , Sergei Ivanovich TVERDOKHLEBOV 5 , Aleksandr Aleksandrovich ZHERAVIN 6 , Lyudmila Nikolaevna BONDAR 1 , Vladimir Mikhaylovich PERELMUTER 1 выполняют замену дефектов скелета и мягких тканей, однако не могут адекватно восстановить тонкую, сложную анатомию челюстно-лицевой области [7].…”
Section: Interaction Of Bioresorbable Composite Implants Made By Soluunclassified
“…В связи с этим в последние десятиле-тия активно изучается возможность использования различных материалов в реконструкции пострезекци-онных дефектов челюстно-лицевой области. К их чис-лу относят различные алло-, ксено-и брефоматериалы, трикальцийфосфаты, гидроксиапатиты, композиты на основе синтетических и/или биологических струк-тур, полимеры, различные металлы и их сплавы [13,14]. Ограниченное применение перечисленных ма-териалов в реконструктивной хирургии обусловлено их недостатками: потенциальными токсичностью и ин-фицированностью, несущими риск развития воспали-тельных осложнений, низкой интеграционной способ-ностью и неадекватностью восстановления каркасной функции резецированного фрагмента черепа [4].…”
Section: результаты и обсуждениеunclassified